Renal Fibrosis : Extracellular Matrix Microenvironment Regulates Migratory Behavior of Activated Tubular Epithelial Cells - Zeisberg, Michael (American Society for Investigative Pathology, 2002)
During progression of chronic renal disease, qualitative and quantitative changes in the composition of tubular basement membranes (TBMs) and interstitial matrix occur. Transforming growth factor (TGF)-β(1)-mediated activation of tubular epithelial cells (TECs) is speculated to be a key contributor to the progression of tubulointerstitial fibrosis. To further understand the pathogenesis associated with renal fibrosis, we developed an in vitro Boyden chamber system using renal basement membranes that partially mimics in vivo conditions of TECs during health and disease. Direct stimulation of TECs with TGF-β(1)/epithelial growth factor results in an increased migratory capacity across bovine TBM preparations. This is associated with increased matrix metalloproteinase (MMP) production, namely MMP-2 and MMP-9. Indirect chemotactic stimulation by TGF-β(1)/EGF or collagen type I was insufficient in inducing migration of untreated TECs across bovine TBM preparation, suggesting that basement membrane integrity and composition play an important role in protecting TECs from interstitial fibrotic stimuli. Additionally, neutralization of MMPs by COL-3 inhibitor dramatically decreases the capacity of TGF-β(1)-stimulated TECs to migrate through bovine TBM preparation. Collectively, these results demonstrate that basement membrane structure, integrity, and composition play an important role in determining interstitial influences on TECs and subsequent impact on potential aberrant cell-matrix interactions.